2018
DOI: 10.2147/cmar.s160379
|View full text |Cite
|
Sign up to set email alerts
|

<em>ITGA7 </em>functions as a tumor suppressor and regulates migration and invasion in breast cancer

Abstract: BackgroundBreast cancer is the most common malignancy in women and the underlying mechanism of breast cancer cell metastasis is still far from uncover. Integrin subunit alpha 7 (ITGA7) is a functioning protein. It has been detected in many malignancies. But the function of ITGA7 in breast cancer is not clear. Our aim is to explore ITGA7 expression and its role in breast cancer.MethodsReal-time PCR was performed to determine ITGA7 expression in BC tissues and normal adjacent tissues. The specific functions of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…The circ_0026782, circ_0001946, circ_0004826, circ_0077837, circ_0030586, circ_0008039, circ_0001346, and circ_0003141 are spliced from ITGA7, CDR1, UTRN, EPB41L2, ABCC4, PRKAR1B, RNF13, and UBAP2, which all play an important effect in tumor proliferation, migration, and metastasis. Bhandari A et al reported that ITGA7 acts as a tumor suppressor and regulates migration and invasion in breast cancer 52 . According to cell proliferation assays as well as the mouse xenograft model, Li et al determined UTRN as a breast cancer suppressor gene both in vitro and in vivo 53 .…”
Section: Discussionmentioning
confidence: 99%
“…The circ_0026782, circ_0001946, circ_0004826, circ_0077837, circ_0030586, circ_0008039, circ_0001346, and circ_0003141 are spliced from ITGA7, CDR1, UTRN, EPB41L2, ABCC4, PRKAR1B, RNF13, and UBAP2, which all play an important effect in tumor proliferation, migration, and metastasis. Bhandari A et al reported that ITGA7 acts as a tumor suppressor and regulates migration and invasion in breast cancer 52 . According to cell proliferation assays as well as the mouse xenograft model, Li et al determined UTRN as a breast cancer suppressor gene both in vitro and in vivo 53 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, hypermethylated SERPINB12 protease inhibitor, located in the serpin gene cluster on chromosome 18, is downregulated in clinical samples which suggests its potential tumor suppressor role . Hypermethylated ITGA7 belongs to the integrin family and is a newly identified tumor suppressor gene that decreases migration and invasion of cancer cells . On the other hand, hypomethylated MMP1 is a potent oncogene promoting metastasis and multi‐drug resistance, and hypomethylated PLEKHA5 facilitates metastasis to the brain .…”
Section: Discussionmentioning
confidence: 99%
“…A lot of studies have discovered many oncogenes and tumour suppressor genes, which are acknowledged to be related to the occurrence of breast cancer. [7][8][9] Long noncoding RNAs as a heterogeneous class of noncoding RNAs, which are longer than 200 nucleotides, have been identified to involve in many human diseases, including tumorigenesis. 10,11 A few long noncoding RNAs (lncRNAs) have been identified as oncogenic or suppressor genes and regulate the progress of breast cancer.…”
Section: Foxd3mentioning
confidence: 99%
“…[7][8][9] Long noncoding RNAs as a heterogeneous class of noncoding RNAs, which are longer than 200 nucleotides, have been identified to involve in many human diseases, including tumorigenesis. In recent years, increasing long noncoding RNA (lncRNA) has been discovered to be related to tumorigenesis, progression, and prognosis.…”
mentioning
confidence: 99%